El comercio de Filipinas en el tránsito al siglo XVIII: la política comercial china / Trade in The Philippines at the Turn of the 18th Century: The Commercial Policy of China (Vegueta: Anuario de la Facultad de Geografía e Historia, 2020)
A finales del siglo XVII los comerciantes de Filipinas detectaron un problema creciente: la calidad de las mercancías chinas había caído espectacularmente. Con esta investigación damos respuesta no solo al porqué de esa peculiaridad, sino también a las implementaciones que se intentaron aplicar. Para ello hemos profundizado en la documentación existente, especialmente en los expedientes de comercio de Filipinas con Nueva España y los correspondientes Cabildos abiertos que se realizaron para tal fin. El resultado podemos dividirlo en dos grupos de soluciones: las burocráticas y la búsqueda de nuevos mercados en los distintos puertos asiáticos. / At the end of the 17th century merchants in the Philippines detected a growing problem: the quality of Chinese merchandise had fallen off dramatically. In this investigation, we offer both an explanation for this particular situation, but also the implementations that were attempted to address it. To do so, we have delved into existing documentation, in particular the trade records of the Philippines with New Spain and the corresponding open Cabildos that were set up for that purpose. The results can be divided into two groups of solutions: either bureaucratic ones or the search for new markets in other Asian ports.